Characterization of an X-chromosomal non-mosaic monosomy (59, X0) dairy heifer detected using routinely available single nucleotide polymorphism genotype data. Issue 3 (1st March 2017) - Berry, D. P.; Wolfe, A.; O'Donovan, J.; Byrne, N.; Sayers, R. G.; Dodds, K. G.; McEwan, J. C.; O'Connor, R. E.; McClure, M.; Purfield, D. C.
Abstract: Evidence exists from a range of species on the impact of karyotype abnormalities on reproductive performance. Despite this, cytogenetic analyses of cattle, especially females, are not routinely undertaken. Genome-wide single nucleotide polymorphism (SNP) genotype data are now, however, routinely being generated in many species globally at a relatively low cost. The objective of the present study was to evaluate the potential of routinely available SNP genotype data to identify sex-chromosome aberrations using X chromosome monosomy 59, X0 as a case study for illustration. A single 2.5-yr old Holstein-Friesian heifer was detected with a mean allelic intensity of SNP on the X chromosome almost 17 standard deviations less than the mean of other genotyped females ( n = 103, 326). Following cytogenetic analysis (10 replicates by karyotyping and a further 140 by FISH), the female was deduced to be a non-mosaic 59, X0. The female had never produced a calf and, although gross examination revealed no physical abnormalities, she was smaller in size than expected based on her breed and age. Given the age of the animal at slaughter, the uterus and uterine tubes appeared immature and inactive. The oviduct appeared normal while the single ovary present contained a markedly reduced number of follicles. There was, however, some evidence of prior ovulation and formation of corpora lutea. The approach proposed in the present study to identify allosome aneuploidy from routinely available genotype data can be used to screen for such abnormalities at no additional cost to the breeder or producer.